Drug Utilization Pattern in Patients with Different Types of Dementia in Western India. (27th August 2014) - Patel, Mansi; Joshi, Anuradha; Suthar, Jalpa; Desai, Soaham
Abstract : Background. Dementia is one of the most frequent disorders among elderly patients, reaching to epidemic proportions with an estimated 4.6 million new cases globally annually. Partially effective treatments are available for dementia. Aims & Objectives. We aim to study drugs used in dementia and find out frequency of types of Dementia. Method. This was an observational study conducted at rurally based tertiary care hospital. Prospective data was collected from outpatient department, while retrospective data was collected from medical records. Descriptive statistics were used to analyze data. Result. Total 125 prescriptions of patients diagnosed with dementia were analyzed. Alzheimer's dementia was most common (65.6%), followed by vascular dementia (21.6%), and frontotemporal dementia (10.4%), with the rarest being Lewy body dementia in (2.4%) cases. 60.57% of patients were males. Mini Mental Score Examination mean score was 15.93 ± 1.37. Frontal Battery Assessment mean score was 4.75 ± 1.01. Prescribed drugs were Donepezil (68.49%), Rivastigmine (13.63%), Donepezil + Memantine (6.43%) and Galantamine (12.83%), Quetiapine (38.46%), Lorazepam (23.07%), Clozapine (11.53%), Escitalopram (10.25%), Haloperidol (3.84%), Zolpidem, Sertraline, Olanzepine (2.56%), Nitrazepine, Lamotrigine, Fluoxetine, Tianeptine (1.28%), Folic acid, and Vitamin B12, respectively. Conclusion. Alzheimer's is the most common type of dementia while Donepezil was the most frequent drug.